PREPARATION OF 99mTc-TRICINE-EDDA-HYNIC-FOLATE, A POTENTIAL RADIOPHARMACEUTICAL FOR RADIODIAGNOSIS OF FOLATE RECEPTORS OVER EXPRESSED CANCER - Martalena Ramli; Rien Ritawidya; Cecep Taufik Rustendi; Titis Sekar Humani; Widyastuti Widjaksana (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
PREPARATION OF 99mTc-TRICINE-EDDA-HYNIC-FOLATE, A POTENTIAL RADIOPHARMACEUTICAL FOR RADIODIAGNOSIS OF FOLATE RECEPTORS OVER EXPRESSED CANCER. Folate receptors (FRs) have been reported to be over expressed on various types of cancers. Therefore, it would be possible for its ligand in this case folic acid, also known as vitamin B9, to be used as delivery agent for diagnosis and therapy of FRs over expressed cancers. The aim of this projectwas to prepare 99mTc radiolabeled folic acid via 6-hydrazinonicotinamido-hydrazido (HYNIC) in the form of 99mTc-tricine-ethylenediamine diacetate-HYNIC-folate (99mTc-tricine-EDDA-HYNIC-folate), which was expected to be potential for radiodiagnosis of the FRs over expressed cancers. Preparation of 99mTc-tricine-EDDA-HYNIC-folate was initiated by preparation of HYNIC-folate by reacting of folate-γ- hydrazide with 6-chloronicotinic acid NHS ester which was then followed by addition of hydrazine-hydrate. The HYNIC-folate was recovered in its HCl salt-form which was then formulated to form a freeze dried kit which consisted of HYNIC-folate, tricine and EDDA (co-ligands) and Sn(II) as reducing agent. The formation of 99mTc-tricine-EDDA-HYNIC-folate was carried out by addition of 99mTc into tricine-EDDA-HYNIC-folate freeze dried kit which resulted in 99mTc-tricine-EDDA-HYNIC-folate with radiochemical purity of 97.0 ± 1.8% met with the requirement of a good radiopharmaceutical (≥ 90%). The stability test showed that the 99mTc-tricine-EDDA-HYNIC-folate was still intact (radiochemical purity 95%) when stored at 37 °C for four hours.